Design and test of the key components for a combing-type tobacco harvester - Sun, Chaoran; Tan, Shaohui; Sun, Songling; Xiao, Mingtao; Chen, Limei; Ai, Wenke; Qiu, Zhihua; Jiang, Ping; He, Yang (International Journal of Agricultural and Biological Engineering, 2024)
In response to the problems of low efficiency, high labor intensity, and low mechanization in manual tobacco harvesting, a comb-off tobacco picking device for southern hilly tobacco areas was designed following the agronomic requirements and the principle of manual picking of tobacco harvesting in southern China. The device was composed of the power chassis, picking mechanism, and storage mechanism. This study involved the theoretical analysis, structural design, and modeling of the key components, such as chassis structure, combing-type picking mechanism, and power synchronization mechanism. The results of the motion analysis and calculation of the picking process demonstrated that the adjustment range of the comb chain elevation angles was from 12.4° to 20.9°, the comb rod installation distance was 76.2 mm, and the synchronizing mechanism transmission ratio was 3:10. One-factor test and three-factor three-level orthogonal test was performed with the forward speed of the chassis, the distance between the picking device baffles and the elevation angle of the chain with the combing bar as test factors, and the rate of broken and missed tobacco picking as evaluation indicators. It was revealed that the optimal combination of the forward speed of the chassis, the distance between the baffles, and the chain elevation angle were 1.5 km/h, 75 mm, and 12.4°, respectively. Moreover, verification tests suggested that the breakage rate of tobacco leaves was 9.99%, and the probability of missed tobacco picking was 7.31%, both of which satisfy the agriculture requirements and the operational requirements in the agricultural machinery certification syllabus.Keywords: harvesting machinery, leaf tobacco, combing-type, tiered harvest, synchronizing mechanismDOI: 10.25165/j.ijabe.20241701.8324Citation: Sun C R, Tan S H, Sun S L, Miao M T, Chen L M, Ai W K, et al. Design and test of the key components for a combing-type tobacco harvester. Int J Agric & Biol Eng, 2024; 17(1): 145-153.